1994
DOI: 10.1126/science.8122112
|View full text |Cite|
|
Sign up to set email alerts
|

Fusion of a Kinase Gene, ALK , to a Nucleolar Protein Gene, NPM , in Non-Hodgkin's Lymphoma

Abstract: The 2;5 chromosomal translocation occurs in most anaplastic large-cell non-Hodgkin's lymphomas arising from activated T lymphocytes. This rearrangement was shown to fuse the NPM nucleolar phosphoprotein gene on chromosome 5q35 to a previously unidentified protein tyrosine kinase gene, ALK, on chromosome 2p23. In the predicted hybrid protein, the amino terminus of nucleophosmin (NPM) is linked to the catalytic domain of anaplastic lymphoma kinase (ALK). Expressed in the small intestine, testis, and brain but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
1,585
2
24

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,206 publications
(1,622 citation statements)
references
References 26 publications
11
1,585
2
24
Order By: Relevance
“…The ALK gene rearrangement was originally discovered in anaplastic large cell lymphoma, and the NPM1 gene was its most common translocation partner. 11 Subsequently, recurrent ALK chimeric oncogenes involving diverse partner genes (RanBP2, CLTC, CARS, and others) were identified in inflammatory myofibroblastic tumors. [15][16][17][18] More recently, the ALK gene has been shown to be involved in small subsets of epithelial malignancies, including carcinomas of pulmonary, esophageal, mammary gland, and gastrointestinal origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALK gene rearrangement was originally discovered in anaplastic large cell lymphoma, and the NPM1 gene was its most common translocation partner. 11 Subsequently, recurrent ALK chimeric oncogenes involving diverse partner genes (RanBP2, CLTC, CARS, and others) were identified in inflammatory myofibroblastic tumors. [15][16][17][18] More recently, the ALK gene has been shown to be involved in small subsets of epithelial malignancies, including carcinomas of pulmonary, esophageal, mammary gland, and gastrointestinal origin.…”
Section: Discussionmentioning
confidence: 99%
“…11 Subsequently, ALK rearrangements were found in several phenotypically different hematologic neoplasms [12][13][14] and in histogenetically unrelated inflammatory myofibroblastic tumor. [15][16][17][18] Recently, ALK rearrangements and EML4-ALK and KIF5B-ALK fusions were discovered in a subset of non-small cell lung carcinomas; 19,20 proteomics reports suggested a possible TPM4-ALK fusion in esophageal carcinoma; 21,22 and an exon array profiling study demonstrated the EML4-ALK fusion in 2.5% of breast and colon cancers.…”
mentioning
confidence: 99%
“…It was initially identified as part of the oncogenic nucleophosmin-ALK fusion protein resulting from the t(2;5) translocation that is frequently associated with anaplastic large-cell lymphoma (Morris et al, 1994). Nucleophosmin allows dimerization of the fusion protein, causing constitutive activation of ALK kinase and downstream activation of phospholipase C-g, PI3K, STATs and pp60c-src (Allouche, 2007).…”
Section: Dependence Receptors: a Short Historymentioning
confidence: 99%
“…T-cell lymphomas (TCLs) that express the kinase represent a prototypic ALK-driven malignancy (Chiarle et al, 2008;Li and Morris, 2008). The expression of ALK results in the affected CD4 þ T lymphocytes from translocations involving the ALK gene and several different partners, by far the most frequently, the nucleophosmin (NPM) gene (Morris et al, 1994;Shiota et al, 1994). The NPM/ ALK chimeric protein is constitutively expressed and activated through autophosphorylation (Shiota et al, 1994;Morris et al, 1997).…”
Section: Introductionmentioning
confidence: 99%